2015
DOI: 10.3109/10428194.2015.1007507
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses cell growth of human chronic myeloid leukemia cells via its inhibition of the interleukin-6/Janus activated kinase/signal transducer and activator of transcription 3 signaling cohort

Abstract: Matrine, alkaloid isolated from Sophora flavescens, is known to be pleiotropic by exerting anti-inflammatory, anti-oxidation, as well as anti-cancer effects. However, the precise molecular targets or pathways responsible for its activities still remain unclear. The present study aimed to determine the underlying mechanisms of matrine in inhibiting the chronic myeloid leukemia cells (CML). It was observed that matrine treatment significantly suppressed CML cells proliferation, induced apoptosis and resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…According to our and others’ previous studies, the antioxidative and cardioprotective activities of matrine were featured 18, 19, 20. Several previous studies indicated that matrine regulated some protein kinases, such as AMP‐activated protein kinase and Janus‐activated kinase 21, 22. The pharmacological activities of matrine‐type alkaloids may be similar because they share several of the same key molecular structures 23.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…According to our and others’ previous studies, the antioxidative and cardioprotective activities of matrine were featured 18, 19, 20. Several previous studies indicated that matrine regulated some protein kinases, such as AMP‐activated protein kinase and Janus‐activated kinase 21, 22. The pharmacological activities of matrine‐type alkaloids may be similar because they share several of the same key molecular structures 23.…”
Section: Introductionmentioning
confidence: 81%
“…[18][19][20] Several previous studies indicated that matrine regulated some protein kinases, such as AMPactivated protein kinase and Janus-activated kinase. 21,22 The pharmacological activities of matrine-type alkaloids may be similar because they share several of the same key molecular structures. 23 Thus, it is reasonable for us to speculate that the matrine-type alkaloids may suppress AGEs-induced oxidative stress by affecting MKKs, which further regulates p38 MAPK/Nrf2 signaling.…”
mentioning
confidence: 99%
“…Furthermore, JAK/STAT signaling pathway has been implicated in transmission of information carried by cytokines. It is reported that JAK/STAT3 pathway can be activated by IL6, thus contributes to the CML development (17). Kumar et al (25), also demonstrated that IL-6 can induce JAK/STAT and MAPK pathways, thus have a key role in deciphering the CML progression stages.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, luciferase reporter assay was performed to investigate whether interleukin-6 (IL6) was a target of miR-574-3p. Besides, it is reported that IL6 can regulate the activation of JAK/STAT3 pathway in CML development (17), thus the regulatory relationship between miR-574-3p and IL6/Janus kinase/signal transducer and activator of transcription-3 (JAK/STAT3) pathway was explored. All efforts of our study were to elucidate the potential roles and regulatory mechanism of miR-574-3p in CML development.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the regulation of IL-6 expression and activation of the JAK1/STAT3 signaling pathway (17–19,24). A number of previous studies have reported the effects of matrine on NSCLC cells with the T790M mutation, including H1975 cells, in the presence or absence of a TKI.…”
Section: Discussionmentioning
confidence: 99%